The effect of different frequency of whole body vibration in diver` flexibility and explosive strength of lower limbs - Dallas, G.; Paradisis, G.; Tsiganos, G.; Argeitaki, P.; Smirniotou, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Flexibility and explosive strength of lower limbs are significant factors in diving. The purpose of this study was to examine the acute effect of different Whole Body Vibration (WBV) frequencies on diver`s flexibility and explosive strength of lower limb. Methods: Eighteen male and female competitive divers (Mage 15.00±4.47 years, body mass 48.61±14.97 Kg, Height 159.38±13.36 cm and Body fat % 14.15±5.31) volunteered to participate in this study. The sample was assessed under different intervention programs a) vibration program with low frequency (30 Hz) and amplitude (2 mm) (LFA) b) vibration program with high frequency (50 Hz) and amplitude (4 mm) (HFA) and c) Non Vibration program (NVG). Each intervention program consisted of a single repeated bouts session lasting for 2 minutes. The following tests were done before-pre and after-post each intervention program: a) flexibility (sit & reach test), and b) explosive strength of lower limbs under 3 different tests a) Squat Jump (SJ), b) Counter Movement Jump (CMJ), c) Single Leg Jump for the Right (RL) and Left Leg (LL). Results: A two-way ANOVA (day*trials) with repeated measures on both factors was used. Univariate analysis with Bonferonni adjustments (.05/3) were selected as post hoc tests. There was significant interaction between day * trials with respect to: a) sit & reach (p=.001), b) SJ (p=.004), c) RL (p=.017). However, no interaction effect between day * trials was found with respect to a) CMJ and LL (p>.05). Discussion: The results support that both vibration intervention programs showed a great percentage of improvement on flexibility compared to NVP. Further, vibration programs is an effective method to maintain the gain in explosive strength of lower limbs immediately after, whereas NVP failed to maintain the initial values in this test. The athletes underwent the vibration programs showed an improvement on flexibility and explosive strength, while the athletes of NVP showed no significant effect between pre and post sessions. Further, the improvement through vibration programs was significant higher than the NVP.